PENGARUH PERUBAHAN KINERJA PERUSAHAAN TERHADAP PERUBAHAN STRUKTUR DEWAN KOMISARIS - Pratiwi, Tika Ratna; Laksito, Herry (Diponegoro Journal of Accounting, 2014)
This study aimed to analyze the influence of changes in firm performance on changes in board structure. The data which are used in this study were obtained from the Indonesia Stock Exchange from 2007 to 2012. Samples were selected by purposive sampling method and finally obtained 91 manufacturing companies that fulfill the criterias.The data were analyzed using logistic regression analysis model. The result shows that changes in ROA have significantly positive impact on the changes in the number of commissioners, while changes in ROE have significantly negative impact on the changes in the number of commissioners.